Unreliable Guides: Introducing, Mapping and Performing Interiors - Hollis, Edward (UI Scholars Hub, 2018)
Whether as teachers listening to students, as designers ‘pitching’ designs to clients, or critics writing about historical spaces, we use speech and gesture to describe interiors. We assume that the interior does not speak on it’s own, but must be spoken for. How do designers, curators, and guides talk interiors into existence? How, more generally should we speak of the interior? This paper will explore this issue through reflection on three encounters between space, speech and gesture in the form of guided tours of historic interiors. It will frame these questions with four contexts: firstly, the evolution of the historical concept of the guide; secondly, the idea of the interior as portraiture; thirdly, the evolution, particularly in the twentieth century, of performance (particularly theatrical performance) and finally, the distinction between the interior as image, and the interior as inhabitation.